Gestão de processos de negócio: estudo da tecnologia BPM/SOA na implantação de sistemas integrados de gestão-ERP - Amaral, Francisco Piedade (2010)
Along with the rising number of organizations adopting the process oriented managing model, the IT area has been challenged to adapt to this new context, providing integrated systems to support the business model. This adaptation requires changes in the management model, strong alignment with the business and new IT consultant profile. The concept of Business Process Management (BPM) and the concept of Service Oriented Architecture (SOA) has been the way solution providers companies for integrated business management applications (ERP Systems) have adopted to enable Process-oriented management model. This new methodology requires a new way of implementing ERP Systems, based on business alignment, process integration and a new profile for IT consultants is demanded. With the integrated use of BPM/SOA approach, organizations can define and optimize business process to implement software systems able to perform the orchestration of their activities for a improved competitiveness in the market place